2019
DOI: 10.1111/gtc.12708
|View full text |Cite
|
Sign up to set email alerts
|

FAM48A mediates compensatory autophagy induced by proteasome impairment

Abstract: Maintaining protein homeostasis is central to cell survival. The ubiquitin-proteasome system and autophagy play pivotal roles in protein quality control through protein degradation. Activities of these degradative pathways are carefully orchestrated, and autophagy is up-regulated during proteasome dysfunction for cellular homeostasis. However, the mechanism by which proteasome impairment induces compensatory autophagy has remained largely elusive. Here, we show that FAM48A mediates autophagy induction during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…More recently, p38IP/hSpt20 was also associated with another type of autophagy, known as compensatory autophagy, which is induced after proteasome dysfunction. In this type of autophagy, p38IP, also known as FAM48A [67], accumulates in cells when the proteasome is inhibited and drives the correct localization of Atg9 into recycling endosomes, which is required for the compensatory autophagy that is induced upon proteasome impairment [67]. These combined studies demonstrated that p38IP/hSpt20/FAM48A can bind to proteins other than those in the SAGA complex and can act in cellular processes distinct from transcription.…”
Section: Spt20/p38ip Has Transcription-independent Functionsmentioning
confidence: 99%
“…More recently, p38IP/hSpt20 was also associated with another type of autophagy, known as compensatory autophagy, which is induced after proteasome dysfunction. In this type of autophagy, p38IP, also known as FAM48A [67], accumulates in cells when the proteasome is inhibited and drives the correct localization of Atg9 into recycling endosomes, which is required for the compensatory autophagy that is induced upon proteasome impairment [67]. These combined studies demonstrated that p38IP/hSpt20/FAM48A can bind to proteins other than those in the SAGA complex and can act in cellular processes distinct from transcription.…”
Section: Spt20/p38ip Has Transcription-independent Functionsmentioning
confidence: 99%